Fundamental of Entrepeneurship ENT300 Business Plan Business: Hijabista Boutique / Nur Syahirah Halim - Halim, Nur Syahirah (2020)
Hijabista Boutique is known as a boutique that has a unique design and has its own criteria. Hijabista out there can be our main customer to purchase hijab and any kind of outfit such dress, blouse, skirts, top and other fashion clothing. Clothing selections and exclusive personal style services, which include a detailed style assessment, will ensure that our customers are well dressed. My design will carry Ready-to-Wear (RTW) design and casual/contemporary apparel & and accessories for women, and will be the exclusive attire. I will provide services such as Style Assessments, alterations, personal shopping, and special ordering to customers during store hours and by personal appointments. Stylist who are trained within the image industry will be available to customers on a daily basis. My innovative style and educational emphasis in helping women develop their personal styles will enhance our reputation as a truly unique boutique.